Dielectric material measurement method: a review / Muhammad Al-Hadi Zable … [et al.] - Zable, Muhammad Al-Hadi; Ismail Khan, Zuhani; Abdul Rashid, Nur Emileen; Zakaria, Nor Ayu Zalina; Ibrahim, Idnin Pasya; Ab Rahim, Siti Amalina; Mahmood, Mohd Khairil Adzhar (UiTM Press, 2023)
Non-destructive testing (NDT) is one of many techniques that have been developed over the years to facilitate the process of evaluating and inspecting material properties in a wide range of applications. These techniques can be used on materials such as metals, ceramics, composites, and coatings to assess the material properties without modifying the entire properties and damaging the material structure. Owing to a few limitations associated with NDT methods toward dielectric materials, microwave-based testing such as microwave non-destructive testing (MNDT) appears to be recognized and preferred for penetrating the dielectric material. The method, which implies employing high-frequency energy ranging from 300 MHz to 300 GHz, could extract the dielectric properties of permittivity and permeability, which will be important in characterizing dielectric materials. In this paper, the four categories of resonator method, resonant perturbation method, reflection method, and transmission-reflection method within each measurement system have been reviewed. Each of the measurement methods serves particular principles and applications with respect to its frequency range, benefits, constraints, type of material tested, and accuracy. Based on the research findings, these methods have contributed to various fields of dielectric material characterization (solids, liquids, and gases), inspection of layered composites, surface crack detection, biological application, and also sensors design.